General auditory processing, speech perception and phonological awareness skills in Chinese–English biliteracy. (28th September 2011) - Chung, Kevin K. H.; McBride‐Chang, Catherine; Cheung, Him; Wong, Simpson W. L.
<x xml:space="preserve">Abstract</x> This study focused on the associations of general auditory processing, speech perception, phonological awareness and word reading in Cantonese‐speaking children from Hong Kong learning to read both Chinese (first language [L1]) and English (second language [L2]). Children in Grades 2–4 (N=133) participated and were administered measures of IQ, word reading, phonological awareness, speech perception and auditory processing in both L1 and L2. Auditory processing uniquely explained both L1 and L2 word reading. While L1 speech perception accounted for unique variance in L1 word reading, L2 phonological awareness explained unique variance in L2 word reading. In cross‐language comparisons, L1 phonological awareness and speech perception were uniquely associated with L2 word reading, suggesting cross‐language transfer from L1 to L2 only. Results underscore the importance of auditory processing for reading across variable learning contexts.